Revisioning the Myth of King Ahab in Paulo Coelho’s The Devil and Miss Prym - Krisnawati, Diyan; Wijanarka, Hirmawan (Universitas Sanata Dharma, 2014)
Many people think that myth refers to only folklores or legends which have long been existed in a society. What if myth turns out to be more than just an ancient story our parents tell us? Through Paulo Coelho’s The Devil and Miss Prym, this article tries to find out the answer. In the novel, a ruthless person was described ruling a village named Viscos. He was Ahab, a man full of arrogance and meanness. He governed the village whose inhabitants are only a few. The existence of this Ahab is reminiscent of another Ahab found in the Bible. However, Coelho presents a surprise for the readers by creating a different Ahab, changing Ahab to a generous and pleasant man. This re-visioning (re-observing and re-examining from a different point of view) reveals the fact that the story of Ahab in the novel is more than merely an old story found in the Bible. Under the light of Roland Barthes’s theory of myth, this article aims at revealing how The Devil and Miss Prym re-visions the myth of King Ahab in the Bible. Myth in this novel can also be classified as the myth of freedom since it breaks some accepted concepts in society.Keywords: Re-vision, Myth, King Ahab